SOCIAL CHANGES TOWARDS WOMEN'S PROGRESS IN EGYPT - Al Anshariyah, Ria Rufaidah; Mubarokah, Lailatul; Holel, Abdul (Pascasarjana UIN Kiai Haji Achmad Siddiq Jember, 2023)
Patriarchal culture is very strong in the Middle East where Middle Eastern society wants to eliminate the culture little by little by means of social change under the pretext of community empowerment, Social movements bring change with one of the movements carried out by Qasim Amin, he was the first person to voice women's emancipation as women can develop and progress from time to time without losing their identity. The results of the study show that social change in Egypt has increased women's participation in various aspects of life, including education, work, and politics. However, there are still several challenges that must be overcome, such as economic inequality and social discrimination that still occur. Social change in Egypt has brought significant progress for women, but further efforts are still needed to overcome the social and economic inequality that still exists. This study also shows that there is still much room for further research on social change and women's progress in Egypt.